2019
DOI: 10.1128/jb.00014-19
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Can Inhibit Growth of Streptococcal Species via Siderophore Production

Abstract: Cystic fibrosis (CF) is a genetic disease that causes patients to accumulate thick, dehydrated mucus in the lung and develop chronic, polymicrobial infections due to reduced mucociliary clearance. These chronic polymicrobial infections and subsequent decline in lung function are significant factors in the morbidity and mortality of CF. Pseudomonas aeruginosa and Streptococcus spp. are among the most prevalent organisms in the CF lung; the presence of P. aeruginosa correlates with lung function decline, and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 67 publications
4
21
0
Order By: Relevance
“…replicated their genomes (a surrogate for growth) 40-to 60-fold faster than P. aeruginosa (72). This finding would be consistent with the published observations that coculture of Streptococcus with P. aeruginosa enhances the growth of the Streptococcus with no obvious benefit to P. aeruginosa growth (42,67).…”
Section: P Aeruginosa Impacts Streptococcal Viability and Growthsupporting
confidence: 90%
See 2 more Smart Citations
“…replicated their genomes (a surrogate for growth) 40-to 60-fold faster than P. aeruginosa (72). This finding would be consistent with the published observations that coculture of Streptococcus with P. aeruginosa enhances the growth of the Streptococcus with no obvious benefit to P. aeruginosa growth (42,67).…”
Section: P Aeruginosa Impacts Streptococcal Viability and Growthsupporting
confidence: 90%
“…In contrast to the negative interactions described above, recent studies have found that P. aeruginosa can also enhance Streptococcus growth through one or more currently undescribed pathways (42,44,47,48,67). For example, our group demonstrated that P. aeruginosa clinical and laboratory strains can enhance the growth of multiple oral Streptococcus spp., including members of the SMG, through a currently unknown mechanism (67).…”
Section: P Aeruginosa Impacts Streptococcal Viability and Growthmentioning
confidence: 72%
See 1 more Smart Citation
“…polymicrobial communities can have profound and diverse consequences on bacterial growth (8)(9)(10), as well as on disease progression and therapeutic outcomes (6,11).…”
mentioning
confidence: 99%
“…Microbes in host-pathogen [15], soil [16], and marine systems [17] have adapted to modulate local iron conditions through the evolution of siderophores. Siderophores are small organic molecules with high iron binding affinity [18].…”
Section: Introductionmentioning
confidence: 99%